Palestinian Clusters: From Agglomeration to Innovation - Sultan, Suhail S.; Pieter van Dijk, Meine (European Scientific Journal, ESJ, 2017)
This study identifies the advantages, the constraints, as well as the right promotion policies necessary to foster the development of clusters. After a literature review, data were collected through field visits on five important clusters. Fifty cluster firms were surveyed to assess their performance. Semi-structured interviews were held with ten key policy decision makers. Focus group discussions were held, discussing with a group of 10 participants an assessment of the five clusters. The research shows important differences between the five clusters studied. It points to constraining factors, such as a lack of closer collaboration between firms themselves and between firms and universities, which could lead to innovation. As the size of most of the Palestinian economic entities are micro to small and medium, clustering can help these entities to increase their productivity and thus help in reducing the high unemployment rate among Palestinian youth.